Lymphoepithelial Cyst in the Palatine Tonsil - Fatih Bingöl (Case Reports in Otolaryngology, 2016)
Lymphoepithelial cyst (LEC) is the most commonly encountered congenital neck pathology in the lateral part of the neck. A 66-year-old woman presented to the ENT clinic due to difficulty in swallowing persisting for approximately 1 year. Magnetic resonance imaging revealed a cystic mass at right tonsil. Surgery was performed due to this unilateral tonsillar mass, which was excised together with the right tonsil. LEC was diagnosed at histopathological examination. LEC in the palatine tonsil is rare, and only a few cases have been reported in the literature. We report a rare case of LEC in the palatine tonsil.